Numerical simulation of supersonic and turbulent combustion with trans-verse sonic fuel injection - Kamel, Mohammed; Owis, Farouk; Idres, Moumen; Hashem, Aly (Inderscience Publishers, 2015)
Complicated interacting flow features such as shock-wave, boundary-layer and shock induced combustion are simulated numerically in the current study to investigate the effect of the transverse sonic fuel injection on the air-fuel mixing and flame stabilisation. The flow is modelled using the Reynolds-averaged Navier-stocks (RANS) equations, where chemical kinetics model is employed to compute the finite rates of chemical reactions. Turbulence is modelled using the Baldwin-Lomax algebraic model. Finite-volume scheme is applied where the convective fluxes are discretised by second order accurate Roe’s scheme using MUSCL approach. Second order accurate Runge-Kutta method is used for the time-integration. Turbulent and chemically-reacting supersonic flow of hydrogen-air mixture over a ramp is simulated and the results show good agreement with the experimental data and the published numerical simulations In addition, air-hydrogen flow is studied in a single strut scramjet engine, where mixing and flame holding processes are carried out using fuel transverse sonic injection.